INCLUSION-BASED SCHOOL LEARNING STRATEGY THROUGH PLAY ACTIVITIES AT ANNA HUSADA PAUD BANGKALAN - Surya Kumala Dewi; Fikri Nazarullail; Dwi Nurhayati Adhani (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This research is motivated by the existence of PAUD institutions that are not optimal in implementing learning, especially in inclusion-based PAUD institutions. The purpose of this study was to determine the strategy for implementing learning through play activities at the Anna Husada Inclusion PAUD school. The subjects in this study were Anna Husada's early childhood education staff and students. The research approach used is qualitative with a case study approach. The main data collection techniques used in this study were interviews, observation, and documentation. Data analysis for this research is data collection, data reduction, data presentation and conclusion, as well as recall or validation. The data validation techniques were extended participation, observer persistence, and triangulation. The results showed that the implementation of Anna Husada PAUD inclusive school learning used the central learning model strategy. Play activities that are packaged in the center learning model aim for children to be able to play with a feeling of calm, mingle with their friends and accept each other between normal good friends and those with special needs.